A regional record of expanded Holocene wetlands and prehistoric human occupation from paleowetland deposits of the western Yarlung Tsangpo valley, southern Tibetan Plateau. Issue 1 (July 2016) - Hudson, Adam M.; Olsen, John W.; Quade, Jay; Lei, Guoliang; Huth, Tyler E.; Zhang, Hucai
Abstract: The Asian Monsoon, which brings ~80% of annual precipitation to much of the Tibetan Plateau, provides runoff to major rivers across the Asian continent. Paleoclimate records indicate summer insolation and North Atlantic paleotemperature changes forced variations in monsoon rainfall through the Holocene, resulting in hydrologic and ecologic changes in plateau watersheds. We present a record of Holocene hydrologic variability in the Yarlung Tsangpo (YT) valley of the southern Tibetan Plateau, based on sedimentology and 14 C dating of organic-rich black mats' in paleowetlands deposits, that shows changes in wetlands extent in response to changing monsoon intensity. Four sedimentary units indicate decreasing monsoon intensity since 10.4 ka BP. Wet conditions occurred at ~10.4 ka BP, ~9.6 ka BP and ~7.9–4.8 ka BP, with similar-to-modern conditions from ~4.6–2.0 ka BP, and drier-than-modern conditions from ~2.0 ka BP to present. Wetland changes correlate with monsoon intensity changes identified in nearby records, with weak monsoon intervals corresponding to desiccation and erosion of wetlands. Dating of in situ ceramic and microlithic artifacts within the wetlands indicates Epipaleolithic human occupation of the YT valley after 6.6 ka BP, supporting evidence for widespread colonization of the Tibetan Plateau in the early and mid-Holocene during warm, wet post-glacial conditions.